A tri-band (Ku, K and Ka-bands) shared-aperture reflect-transmit-array based on spatial phase genetic algorithm - Tian, Lu; Zhang, Rui; Wang, Yong; Ren, Yueyan; Yang, Ziwei; Jiao, Kunlong; Li, Haixuan; Xie, Bingchuan (Physica scripta, 2025)
A broadband tri-band shared-aperture reflect-transmit-array (RTA) is presented in this paper. This design is characterized by its simpler structure, tri-band operation and great broadband characteristics. In addition, the spatial phase genetic algorithm (SPGA) is also utilized to optimize the distribution of two kinds of elements to reduce the interference. Due to f max / f min  > 2.3, the hexagonal units are utilized. Two kinds of RTA elements are designed to achieve different reflection characteristics (Element I: reflection in Ku-band; Element II: reflection in Ka-band), and the same transmission performance in K-band. After array optimization using SPGA, this RTA was simulated, manufactured and measured to verify the performance. There is a good consistency between the simulated and measured results. The measurements indicate that the peak gain is 22.15 dBi, 25.09 dBic and 25.57 dBi at 16.5, 25.5 and 34.0 GHz, respectively. The 3 dB gain bandwidth (BW) is 18.93%, 39.12% and 19.80% in Ku-, K-, and Ka-bands, respectively. Furthermore, the 3 dB axial ratio (AR) BW is 31.58% when working at transmission mode. The proposed antenna is anticipated to exhibit considerable potential in multi-band application scenarios.